Descriptive investigation about the use of virtual classrooms at the english teacher training career, Escuela Normal Superior Arturo Capdevila - Ana Inés Iriondo (Ministerio de Educación, Dirección General de Educación Superior, 2018)
This research analyzes and describes the use of virtual classrooms in the English Teachers of ENSAC, giving account of distance learning, mediated by the use of ICT. In this way the work proposes approaches on the limits and benefits of the virtual education in the Teachers of English, specifically under the blended learning (b-learning). The information was obtained from the implementation of observations and questionnaires made to 7 teachers and 49 students. The b-learning mode combines classroom and virtual teaching. Understanding that for this it is fundamental the teaching intervention in the management of contents, tasks, debates as well as the participation of the students. In this sense, the main benefit is that the virtual classroom is a resource designed to promote meaningful, collaborative and participatory learning based on the use of ICT. Regarding the main difficulties of access and use of the virtual classroom are described: limited connectivity and task overload. Finally, research proposes positive contributions to guide teachers in the use of virtual learning environments as a strategy to improve teaching and students in achieving a more dynamic and collaborative learning.